USE OF HERBAL REMEDY URISAN AS BASIC THERAPY FOR GOUT - Tamila Nilovna Khalfina; I G Salikhov; S P Yakupova (Современная ревматология)
Objective: to evaluate the efficacy, safety, and tolerance of the herbal complex Urisan used in patients with gout. Subjects and methods. Thirty allopurinol-untreated patients with a verified diagnosis of gout (by the ACR criteria) were followed up during a relapse-free interval. Subjective appraisals of the tolerance of Urisan were provided by a physician and a patient. General clinical examination, anthropometry, monitoring blood pressure and uric acid (UA) in blood and urine, and lipid metabolism were made to define the efficiency of therapy before and after it. Results. Urisan exhibited a positive effect in reducing the blood levels of UA (p< 0,003). For more detailed evaluation of the effect of Urisan on hyperuricemia, the patients were divided into 3 groups in accordance with the baseline level of UA; positive changes were observed in all the groups. Significantly lower UA levels were seen in Groups 1 and 2 (p< 0,007 and p< 0,04, respectively). The remedy was found to have no effect on UA excretion. Its tolerance was good. Conclusion. Urisan has a positive effect, by lowering hyperuricemia despite the latter's baseline values